On the abscises of the convergence of multiple Dirichlet series - Zadorozhna, O.Yu.; Skaskiv, O.B. (Carpathian Mathematical Publications, 2009)
For multiple Dirichlet series of the form F(s)=_\|n\|=0^∞ a_(n){(λ_(n),s)} we establish relations between domains of the convergence G_c, absolutely convergence G_a and of the domain of the existence of the maximal term G_μ of the series as follows: γ G_cG_a+δ_0 e_1, γ G_μG_a+δ_0 e_1, where e_1=(1,…,1)R^p, δ_0R, by condition _\|n\|→∞ (γ-1)|a_(n)|+δ_0\|λ_(n)\|\|n\|>p; γ G_cG_a+δ; γ G_μG_a+δ, where δR^p, by condition _\|n\|→∞ (γ-1)|a_(n)|+(δ,λ_(n))n_1+...+n_p>1.